2024
DOI: 10.1002/cbdv.202400302
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and Anticoagulant Effects of Two New Phenylpropanoid Sucrose Esters and Other Secondary Metabolites from the Aerial Part of Canna edulis

Thi Van Anh Nguyen,
Thi Minh Hang Nguyen,
Thi Thoa Ha
et al.

Abstract: This study isolated pure compounds from Canna edulis aerial parts and assessed their antiplatelet and anticoagulant potential. Structural elucidation resulted in the identification of two new compounds: caneduloside A (1) and caneduloside B (2), and eleven known compounds: 6’‐acetyl‐3,6,2’‐tri‐p‐coumaroyl sucrose (3), 6¢‐acetyl‐3,6,2¢‐triferuloyl sucrose (4), tiliroside (5), afzelin (6), quercitrin (7),  2‐hydroxycinnamaldehyde (8), cinnamic acid (9), 3,4‐dimethoxycinnamic acid (10), dehydrovomifoliol (11),  4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…8 In 2024, a study showed that DMCA had antiplatelet effects for both ADP and collagen and showed anticoagulant activities. 9 The practical application of chemical substances is always closely related to the interaction between the molecules in the system, and molecular interactions can determine its physical properties such as dissolution, crystal nucleation, and growth. 10,11 However, solubility is a crucial physicochemical characteristic in the crystallization process, which is a key factor in optimizing the crystallization process and predicting the final yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In 2024, a study showed that DMCA had antiplatelet effects for both ADP and collagen and showed anticoagulant activities. 9 The practical application of chemical substances is always closely related to the interaction between the molecules in the system, and molecular interactions can determine its physical properties such as dissolution, crystal nucleation, and growth. 10,11 However, solubility is a crucial physicochemical characteristic in the crystallization process, which is a key factor in optimizing the crystallization process and predicting the final yield.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ferulic acids and various methylated cinnamic acid derivatives, like DMCA, improve cell viability and indirectly increase the expression of various endogenous antioxidant enzymes. , What is more, Zheng et al demonstrated DMCA against adult and larval stages of Plutella xylostella . In 2024, a study showed that DMCA had antiplatelet effects for both ADP and collagen and showed anticoagulant activities …”
Section: Introductionmentioning
confidence: 99%